Analysis Of The Role Of Gamification In Influence Shopping Engagement : Shopee E-Commerce Case Study: English - Muhammad Nurfaiz Athoillah; Anas Hidayat (International Journal of Economics, Business and Innovation Research, 2024)
This research is a study that examines the gamification features in Shopee E-Commerce which are designed to provide new experiences for users in playing games available on Shopee E-commerce. This research aims to examine the influence of gamification on shopping engagement in consumers which will ultimately lead to buying interest. This research uses a quantitative approach with analysis tools using Smart-PLS. The data used is primary data with data collection tools using a questionnaire and data obtained from 210 respondents. The findings in this research are: 1) Shopping gamification, focused attention, shopping enjoyment, and socialness have a positive and significant effect on shopping engagement, 2) shopping engagement has a positive and significant effect on intention to buy.